Unboxing the black box of visual expertise in medicine - Halszka Jarodzka; Henny P.A. Boshuizen (Frontline Learning Research, 2017)
Visual expertise in medicine has been a subject of research since many decades. Interestingly, it has been investigated from two little related fields, namely the field that focused mainly on the visual search aspects whilst ignoring higher-level cognitive processes involved in medical expertise, and the field that mainly focused on these higher-level cognitive processes largely ignoring the relevant visual aspects. Consequently, both research lines have traditionally used different methodologies. Recently, this gap is being increasingly closed and this special issue presents methods to investigate visual expertise in medicine from both research lines, namely those investigating vision (eye tracking, pupillometry, flash preview moving window paradigm), verbalisations, brain activity, and performance measures (ROC analysis, gesture coding, expert performance approach). We discuss the benefits and drawbacks of each method and suggest directions for future research that could help to unbox the black box of visual expertise in medicine.